Serum concentrations of laminin P1 in diabetics with advanced nephropathy. Issue 9 (September 1988) - Pietschmann, P; Schernthaner, G; Schnack, C H; Gaube, S
Abstract : In 97 patients with type I diabetes mellitus, 155 patients with type II diabetes mellitus, and two matched control groups, serum concentrations of laminin P1, a non-collagenous component of basement membranes, were determined by radioimmunoassay to see whether laminin P1 might be a valuable indicator of microangiopathic complications in diabetics. Independent of the type of diabetes, serum laminin concentrations in patients without nephropathy or with early renal damage as assessed by microalbuminuria were comparable with those of the control subjects. Patients with macroproteinuria or with renal insufficiency had significantly increased serum laminin P1 concentrations. Diabetic retinopathy was not found to influence serum laminin P1 concentrations. These data indicate that serum laminin P1 concentrations are increased in advanced diabetic nephropathy.